The Revitalizing Mosque Functions through Ukhuwatul Islamiyah Da‘wah Institution: From Tabligh to Tathwir - Nasriah, St. Nasriah; Hamiruddin (KOMUNIDA : Media Komunikasi dan Dakwah, 2025)
This study analyzes the form of Ukhuwatul Islamiyah's mosque-based da'wah program in Panciro Village, Bajeng District, Gowa Regency. The study focuses on four main dimensions of Islamic da'wah: tabligh (conveying religious messages), irsyad (guidance and counseling), tadbir (management of religious activities), and tatwir (development and innovation of da'wah). Using a quantitative descriptive approach, this study explores the implementation of da'wah functions by the Ukhuwatul Islamiyah Da'wah Institution (LDUI) in strengthening the role of mosques as centers for community development. The results show that LDUI implements integrated da'wah: regular recitations and sermons (tabligh), community assistance (irsyad), participatory management (tadbir), and digital and economic innovation for the community (tatwir). This study confirms a shift in da'wah from a verbalistic orientation towards a transformative mosque-based model that is adaptive to social challenges, making the mosque a center for the spiritual, social, and digital empowerment of the community.